2022
DOI: 10.5603/cj.a2022.0091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heart failure on the clinical profile and outcomes in patients with atrial fibrillation treated with rivaroxaban. Data from the EMIR study

Abstract: Background:The aim of this study was to analyze the impact of the presence of heart failure (HF) on the clinical profile and outcomes in patients with atrial fibrillation (AF) anticoagulated with rivaroxaban.Methods: Observational and non-interventional study that included AF adults recruited from 79 Spanish centers, anticoagulated with rivaroxaban ≥ 6 months before inclusion.Data were analyzed according to baseline HF status.Results: Out of 1,433 patients, 326 (22.7%) had HF at baseline. Compared to patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…In our study, nearly 12% of patients had died at the end of the follow‐up. In the subgroup of HF patients taking rivaroxaban in the ROCKET‐AF trial, the rate of all‐cause death was 5.1 events per 100 patient‐years 11 and in the HF population of the EMIR study, the annual rate of death was 5.5% 18 . As a result, our data were consistent with previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, nearly 12% of patients had died at the end of the follow‐up. In the subgroup of HF patients taking rivaroxaban in the ROCKET‐AF trial, the rate of all‐cause death was 5.1 events per 100 patient‐years 11 and in the HF population of the EMIR study, the annual rate of death was 5.5% 18 . As a result, our data were consistent with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“… 17 This was also in line with the subgroup of patients with HF included in the EMIR study, a Spanish registry of patients with AF treated with rivaroxaban in clinical practice. 18 As a result, our data are representative of anticoagulated patients with HF and AF. On the other hand, previous studies have shown that within the overall HF population, the proportion of patients with HF with reduced ejection fraction is higher than that observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations